Giant nodular pseudoangiomatous stromal hyperplasia of the breast with fibroadenomatoid myxoid changes: a potential pitfall in the differential diagnosis of phyllodes tumor - Roberto José Medeiros; Patricia Z. Rebutini; Thamyres G. V. Vargas; Fabiola Medeiros; Ana Paula M. Sebastião (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT A 21-year old woman presented with a 17-cm left breast mass. Physical examination and ultrasound revealed the mass to be well-circumscribed, homogeneous and freely mobile, suggestive of giant fibroadenoma or phyllodes tumor. The mass was surgically excised and initially interpreted as benign phyllodes tumor. Subsequent slide review established the diagnosis of nodular pseudoangiomatous stromal hyperplasia (PASH) associated with fibroadenomatoid areas and myxoid stromal changes. This case illustrates the difficulty encountered in recognizing nodular PASH. A thorough discussion of the histopathologic differential diagnosis of nodular PASH is provided.